Self-Translated Writing in Academic Writing: Students’ Experiences in the Classroom Setting - Cut Intan Meutia; Rita Mahriza; I Wayan Dirgayasa Tangkas; Meisuri Meisuri (Institut Agama Islam Negeri Imam Bonjol Padang, 2025)
Self-Translated Academic Writing Practice is a bridge or instrument for improved classroom communication. However, only some studies have examined how students incorporate translation into their foreign language writing. The purpose of the present study was to investigate how students engage in translation practice while writing in the classroom. To determine if there were any issues with the writing and translation practices, a brief exploration of experiences was conducted in class. Additionally, the correlation between translation activity and writing was investigated. The participant reported that these issues resulted from her limited vocabulary match due to the English text's readability. The translation procedure improves their English composition skills. According to the study results, more information is required about how self-translation operates in academic contexts; we need to learn more about the situations in which students self-translate when writing academic papers.